KUALITAS PELAYANAN, DAN KEBERAGAMAN PRODUK TERHADAP MINAT BELI KONSUMEN (Studi Kasus Minimarket Koperasi Karyawan Pura Group Kudus) - Ramadhan, Agung Fajar; suhadi, suhadi (Universitas Islam Negeri Sunan Kudus, 2016)
This study aims to determine the effect of Store Atmosphere, service quality, and product diversity on consumer buying interest. This research was conducted at Minimarket Koperasi Karyawan Pura Group. Population in this research is all cash consumer of Minimarket Koperasi Karyawan Pura Group. The sample used amounted to 40 respondents. Data collectiontechniques used were observation, questionnaire, and documentation. Data analysis in this study using the help of SPSS. Data testing techniques used in this study include the validity test, reliability test, classical assumption test, and multiple linear regression analysis to test and prove the research hypothesis. From the results of this study indicate that Store Atmosphere positively and significantly influence on consumer buying interest in Minimarket Koperasi Karyawan Pura Group. This is evidenced by the regression coefficient of 0.367 and the significance value of 0.001 (sig <0.05). While the calculated value obtained is greater than the table that is 3.675> 2.028. Quality of service influence positively and significantly toconsumer buying interest in Minimarket Koperasi Karyawan Pura Group. This is evidenced by a regression coefficient of 0.348 and a significance value of 0.000 (sig <0.05). While the calculated value obtained is greater than the table that is 4.274> 2.028. The diversity of products has a positive and significant effect on consumer buying interest in Minimarket Koperasi Karyawan Pura Group. This is evidenced by the regression coefficient of 0.265 and a significance value of 0.042 (sig <0.05). While the calculated value obtained is greater than the table that is 2.107> 2.028. Based on the determination coefficient test obtained by the percentage influence of Store Atmosphere variables, service quality, and product diversity towardconsumer buying interest by 69.9%.